THE PORTRAIT OF INDUSTRIAL REVOLUTION IN BRITAIN IN WILLIAM WORDSWORTHâ€™S â€œTHE WORLD IS TOO MUCH WITH USâ€ - Rahaden Lingga Bhumi; Rr. Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2021)
The research aimed to discuss the portrait of industrial revolution and symbol inBritain in William Wordsworthâ€™s The World is too Much with Us. The objectivesof the research were to describe how the industrial revolution in Britain portrayedand what the meaning of symbol related to industrial revolution. The themeswould be related to industrial revolution as portrayed in the poem. The theoriesused in this study were setting, industrial revolution, materialism, allusion, andsymbol. The technique of data collecting was library research, while the methodof the method of this research was descriptive. There were three approaches wereused in this study. They were formalistic, historical, and structural approach. Thefirst result of this research showed that industrial revolution in The World is tooMuch with Us contained four issues, that is, political issues, economical issues,transition from nature to technological changes, and the people of natural world.Political issues explained about population, ambition, power abuse, andcampaign. Economical issues explained about the money, labor, and urge.Transition from nature to technological changes explained about the movement ofsociety from ancient to modern era. The people of natural world explained aboutthe people who choose to live in the ancient and be devote their live-in paganism.The second result of this research showed that the symbol related to industrialrevolution in The World is too Much with Us contained three symbols, that is,nature, poverty, greed and possession. Symbol of nature explained about thecondition of an ecosystem and the society in industrial revolution era. Povertyexplained about the poor rural families have been relocated to towns and cities towork in factories. Greed and possession explained about the people are overlyconcern with worldly matters.Keywords: Industrial Revolution, Symbol, Britain